Facilitator Roles in Action Learning for Leadership Development: A Systematic Literature Review - Al Husna; Uwes Anies Chaeruman; Maria Paristiowati; Imam Fitri Rahmadi (Journal of Educational Sciences, 2026)
Despite broad recognition that skilled facilitation is central to Action Learning (AL) effectiveness, no prior systematic review has examined the facilitator’s roles, competencies, strategies, and challenges as its primary unit of analysis. This gap leaves educational institutions without an evidence base for developing and quality-assuring AL facilitation. This study aims to synthesise empirical evidence on how facilitators shape AL processes within leadership development contexts across four dimensions: roles, competencies, facilitative dialogue, and group dynamics management. A Systematic Literature Review following PRISMA 2020 guidelines was conducted. A structured Boolean query was applied to the Scopus database, yielding 25 empirical studies published between 2020 and 2025 after rigorous screening. Thematic analysis identified four key findings: effective facilitators enact multiple roles across a programme arc; facilitation competency requires set design knowledge, questioning mastery, reflective self-monitoring, and organisational navigation; productive dialogue depends on deliberate question sequencing and tolerance for silence; and psychological safety in AL sets is a facilitated achievement, not an inherent property of the format. The findings establish an integrated facilitation competency framework with direct implications for facilitator preparation programmes and institutional AL design. Future research should prioritise longitudinal and experimental designs to strengthen causal evidence for specific facilitation interventions.